The Influence of Sedimentation on the Composition of the Lipoaspirate and the Effects on Further Mechanical Processing - Andreas Eigenberger; Oliver Felthaus; Alexander Bartsch; Tom Schimanski; Kirsten Utpatel; Lukas Prantl (Cells)
Manual processing of lipoaspirate can enhance stem cell concentration, thereby improving the take rate, which still represents a major challenge in autologous fat transfer. However, since the preparation consists of many manual steps that are difficult to standardize, we investigated the influence of residual tumescent solution on the macroscopic and microscopic outcome of the mechanically processed lipoaspirate. Additionally, we investigated whether sedimentation followed by vacuum filtration of the aqueous phase could accelerate processing by replacing the initial centrifugation step. Samples with more than 5% remaining aqueous phase show no clearly defined oil phase, preventing any volume reduction. In contrast, all centrifuged samples produced a clear oil phase. The remaining tissue, as confirmed by both histology and viability assays, was superior to nanofat. Although sedimentation and filtration in the LipoCollector did not sufficiently separate enough aqueous phase from the lipoaspirate, tissue viability was significantly higher compared to our control container. Our findings indicate that centrifugation remains essential for effective aqueous phase separation and further mechanical processing, while the automatic filtration may enhance processing efficiency. These results indicate that further work is needed to simplify mechanical processing, as the outcome can be significantly influenced by parameters such as tumescent impurities.